Strategi Pengembangan Produk Pangan Lokal Tiwul Instan Berbasis Kewirausahaan Sosial KWT di Kabupaten Banjarnegara - Sarno; Muhamad Solekan; Pujiyanto, Muhammad Aris (Universitas Medan Area, 2025)
Banjarnegara district has great potential in social entrepreneurship for economic empowerment through farm women's groups that produce and market instant tiwul from cassava. The development of instant tiwul products is not only being maintained as local wisdom but also being improved for regional food security. Therefore, the potential of instant tiwul needs to be studied further through the right business model for sustainability and increased business income. This study aims to analyze the development strategy of instant tiwul local food products based on social entrepreneurship by the Women Farmers Group (KWT) in Purwanegara District, Banjarnegara Regency. The sampling method used is Purposive Sampling. The sample of this study was 100 people, using the SWOT analysis method to evaluate internal and external factors that affect the performance of instant tiwul products. The results showed that the main strengths of this product lie in high quality, abundant access to raw materials, distinctive taste, and integration of technology in production. However, weaknesses include a relatively expensive selling price, limited product accessibility, and low consumer awareness. Opportunities include wide market potential, government support, and the increasing trend of healthy food consumption. The main threats are competition with modern food products and changes in people's consumption patterns. An effective enhancement strategy, based on quadrant analysis, should focus on strengthening advantages, leveraging market opportunities, and addressing challenges with a comprehensive and adaptive approach, such as market expansion and production capacity enhancement to reach more consumers. Thus, instant tiwul products can achieve sustainable growth and provide significant economic benefits to local communities and improve the welfare of the farm women involved.